Analysis of Maggot Cultivation Management as an Innovation for Organic Waste Management at the Environmental and Forestry Agency (DLHK) Medan, North Sumatra - Tria Syafira Matondang; Yulia Khairina Ashar; Putri Sintia; Viona Pili Anggita; Nazwa Ayudhia Ghani Damani; Deswita Silviani; Salwa Muthi’ah Siregar (PROMOTOR, 2026)
Organic waste management remains a major challenge in environmental pollution control and the implementation of a circular economy in urban areas. Maggot cultivation (Black Soldier Fly larvae) has emerged as an innovative approach capable of converting organic waste into valuable products. This study aims to analyze the governance of maggot cultivation, its ecological and economic benefits, and the challenges encountered in its implementation at the Environmental and Forestry Office (DLHK) of Medan. The research employed an articulation (descriptive qualitative) approach through in-depth interviews, observations of the cultivation process, and field documentation with five informants one key informant, namely the maggot cultivation manager, and four supporting informants directly involved in the management activities. Data validity was maintained through comparison of interviews, observations, and documentation to ensure reliable and accountable information. The results show that the maggot bioconversion process significantly reduces the volume of organic waste by utilizing food scraps as larval feed. Harvested maggots are used as poultry feed and have been proven to increase cost efficiency in livestock farming. The main challenge involves changes in humidity due to weather conditions, necessitating environmental adjustments such as placing media in shaded areas and improving air circulation. Maggot cultivation at the Environmental and Forestry Office of Medan is proven feasible, sustainable, and supportive of organic waste reduction.